Neutrality of State Civil Apparatus in Regional Head Elections - Supriyadi Supriyadi (Faculty of Law, University of Merdeka Malang, 2024)
Abstract: The results of this study conclude that the neutrality of the State Civil Apparatus in the Implementation of Regional Head Elections has not been implemented properly. There are still many ASNs who are not neutral; this is due to the existence of Article 53 of Law No. 4 of 2014 concerning ASNs, which states that the President, as the holder of the highest authority in ASN development, can delegate the authority to determine the appointment, transfer, and dismissal of officials other than the main and middle high-ranking officials. The main functional expertise is the regent/mayor in the district/city (PPK), so with this, the incumbent candidate can use the authority they have to pressure ASN ahead of the Pilkada. Several efforts have been made by the government, such as through laws and joint decrees of the Minister of State Civil Apparatus Empowerment and Bureaucratic Reform, Minister of Home Affairs, Chairperson of the State Civil Apparatus Commission, and Chairperson of the General Elections Supervisory Body. However, in reality, the loyalty factor between superiors and subordinates is an obstacle to creating a neutral position in the implementation of the Regional Head Election because there are still many ASNs who participate in practical politics. This research is a type of Normative Juridical research with a statutory approach method. The nature of this research is descriptive analysis, which intends to provide a systematic factual and accurate picture or painting of the facts, nature, and relationships between the phenomena investigated on how neutrality in ASN in the election of Regional Heads. How to cite item: Supriyadi, S.